CO-CRYSTALS: A REVIEW - Chaudhari, Shilpa; Nikam, Sarika Ankushrao; Khatri, Neetu; Wakde, Shubham (Journal of Drug Delivery and Therapeutics, 2018)
In development of new product major constraints are poor aqueous solubility and low oral bioavailability. Crystallization is one the approach has been used for enhancement of solubility of poorly aqueous soluble drugs also helps to improve physicochemical properties such as melting point, tabletability, solubility, stability, bioavailability and permeability with preserving the pharmacological properties of the active pharmaceutical ingredient. Different methods have been used for the synthesis of cocrystal such as grinding, slurry, antisolvent, hot melt extrusion, sonocrystallization, supercritical fluid, spray drying etc. The article highlights the co-crystallization, its methods and significance.